Short Telomeres Associate with Hyperphosphorylated Tau Burden in Primary Age‐Related Tauopathy. (20th December 2022) - McMillan, Corey T; Adhikari, Bandita; Farrell, Kurt W.; Wolk, David A.; Lee, Eddie B; Crary, John F.; Johnson, F Brad
Abstract: Background: Primary age‐related tauopathy (PART) is characterized by neuropathological hyperphosphorylated tau burden (p‐tau) in the absence of significant amyloid pathology. Aging is a major risk factor for p‐tau that is generally defined chronologically in years since birth. Telomeres shorten with age and various sources of DNA damage and thus telomere lengths (TL) provide an alternative measure of biological age. Additionally, DNA methylation (DNAm) changes over time and may contribute to changes in TL. Together, we hypothesize that shorter mean TL will be associated with increased risk of p‐tau burden and that this process may be mediated by DNAm. Method: We extracted DNA from frontal cortex of 113 individuals (Age=87.3+9.3; 37% Female) that met neuropathological criteria for definite PART. We measured mean TL using qPCR to determine the copy number of telomere repeat DNA in comparison to a single copy gene. The assays were performed in a blinded fashion, and each sample was measured using two different amounts of input DNA to ensure linearity. We also measured bisulfite‐converted DNA methylation using the Illumina MethylationEPIC BeadChip Kit for ∼850K CpGs. P‐tau burden was measured in medial temporal cortex (entorhinal cortex and hippocampus proper) using an Aperio Digital Pathology Slide Scanner. Linear regression related TL to p‐tau burden, adjusting for age. We used eWAS to relate methylation to TL. Lastly, non‐parametric bootstrapping using the mediation package in R was used to evaluate whether TL association with p‐tau burden may be mediated by DNAm. Result: Shorter TL was significantly associated with increased p‐tau burden (B=‐0.28; p=‐.003), including adjustment for age (B=0.003; p=0.003). eWAS identified six CpG sites significantly associated with TL (all q<0.05). Causal mediation analyses identified that two of these CpGs partially mediate the association between TL length and p‐tau burden: 32.5% proportion mediated by cg08701686 ( UNC5D ) and 48.6% proportion mediated by cg24533059 (near IFNGR1 and OLIG3 ). Conclusion: Shorter TL is associated with increased p‐tau pathological burden in PART and may be mediated in part by DNAm at particular loci. These findings support the concept that biological aging, as measured with TL and DNAm, may contribute to tauopathy beyond chronological age effects.